Disorder over the border: spinning the spectre of instability through time and space in Central Asia. Issue 1 (2nd January 2018) - Koch, Natalie
ABSTRACT: Across Eurasia, authoritarian leaders have sought to justify their 'strong-hand' approach to government by framing instability as a security threat and the strong state as a guarantor of political stability. Such 'regimes of certainty' promote a modernist valorization of order, the flip side of which is a demonization of political disorder instability, or mere uncertainty. Examining the spatial and temporal imaginaries underpinning such narratives about in/stability in Central Asia, this paper compares official discourse in Kazakhstan and Uzbekistan, where state-controlled media and official publications have stigmatized political instability in Kyrgyzstan as indicative of the dangers of political liberalization and a weak state. Ostensibly about the 'other', these narratives are also about scripting the 'self'. I argue that official interpretations of 'disorder over the border' in Kyrgyzstan are underpinned by a set of spatial and temporal imaginaries that do not merely reflect regional moral geographies, but actively construct them.